Changes in the Isotopic Signature of Atmospheric Nitrous Oxide and Its Global Average Source During the Last Three Millennia. Issue 18 (24th September 2018) - Prokopiou, M.; Sapart, C. J.; Rosen, J.; Sperlich, P.; Blunier, T.; Brook, E.; van de Wal, R. S. W.; Röckmann, T.
Abstract: Nitrous oxide (N2 O) is a strong greenhouse gas whose mole fraction in the atmosphere has increased over the industrial period. We present a new set of isotope measurements of N2 O in air extracted from ice cores covering the last 3, 000 years. For the preindustrial (PI) atmosphere, we find an average N2 O mole fraction of (267 ± 1) nmol/mol and average tropospheric N2 O isotopic values of δ 15 N av PI = (9.5 ± 0.1)‰, δ 18 OPI = (47.1 ± 0.2)‰, δ 15 N α PI = (17.8 ± 0.4)‰, and δ 15 Ν β PI = (1.2 ± 0.4)‰. From PI to modern times all isotope signatures decreased with a total change of δ 15 N av = (−2.7 ± 0.2)‰, δ 18 O = (−2.5 ± 0.4)‰, δ 15 N α = (−2.0 ± 0.7)‰, and δ 15 Ν β (−3.5 ± 0.7)‰. Interestingly, the temporal evolution is not the same for δ 15 N av and δ 18 O. δ 18 O trends are relatively larger during the early part, and δ 15 N av trends are larger during the late part of the industrial period, implying a decoupling of sources over the industrial period. Using a mass balance model, we determined the isotopic composition of the total average N2 O source. Assuming that the total present source is the sum of a constant natural source and an increasing anthropogenic source, this anthropogenic source has an isotopic signature of δ 15 N av source, anthrop = (−15.0 ± 2.6)‰, δ 18 Osource, anthrop = (30.0 ± 2.6)‰, δ 15 N α source, anthrop = (−4.5 ± 1.7)‰, and δ 15 N β source, anthrop = (−24.0 ± 8.4)‰. The 15 N site preference of the source has increased since PI times, which is indicative of a relative shift from denitrification to nitrification sources, consistent with agricultural emissions playing a major role in the N2 O increase. Key Points: The isotopic composition of nitrous oxide in the preindustrial period was determined with high precision The isotopic composition of nitrous oxide changed during the transition to the industrial period The temporal evolution of δ 15 N av is different from that of δ 18 O implying a decoupling of sources over the industrial period